2015
DOI: 10.1080/02699931.2015.1070792
|View full text |Cite
|
Sign up to set email alerts
|

Self-directedness and the susceptibility to distraction by saliency

Abstract: People with low Self-directedness (SD) tend to explain their behaviour as being significantly influenced by events in the external environment. One important dimension of external cues is their level of salience: highly salient external stimuli are more likely to capture attention, even when such stimuli are not relevant to goals. We examined whether adults reporting low SD would exhibit greater susceptibility to distraction by highly salient external stimuli. Fifty-four (42 males) subjects completed the Atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…These pictures were divided into high ( n = 20) and low ( n = 20) salience categories based on previous validation [Musolff, ]. We explained the salience as “a property inherent to the stimulus, intended to attract and maintain participants' attention to the stimulus.” Behavioral characterization of the salience effect of the stimuli used here has been provided by Dinica et al [], who suggested that high salience (hs) stimuli are characterized by high stimulus complexity, high arousal, and a high degree of positive valence compared to low salience (ls) pictures, in which emotionally neutral content is depicted. Half of the selected pictures were preceded by a visual cue (expectancy period) and half were presented instantly following a fixation trial with no preceding visual cues ( n = 10 hs and n = 10 ls pictures).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These pictures were divided into high ( n = 20) and low ( n = 20) salience categories based on previous validation [Musolff, ]. We explained the salience as “a property inherent to the stimulus, intended to attract and maintain participants' attention to the stimulus.” Behavioral characterization of the salience effect of the stimuli used here has been provided by Dinica et al [], who suggested that high salience (hs) stimuli are characterized by high stimulus complexity, high arousal, and a high degree of positive valence compared to low salience (ls) pictures, in which emotionally neutral content is depicted. Half of the selected pictures were preceded by a visual cue (expectancy period) and half were presented instantly following a fixation trial with no preceding visual cues ( n = 10 hs and n = 10 ls pictures).…”
Section: Methodsmentioning
confidence: 99%
“…Dopaminergic drugs have been found to alter striatal connectivity to subcortical and cortical targets [Metzger et al, ], both during rest and during preceding attention, along with altered attentional responses during a similar experiment [Graf et al, ]. Furthermore, we previously found participants with low self‐directedness personality to be more distracted by high‐salience pictures as compared to low‐salience pictures, using the Attention Modulation by Salience Task, which suggested that personality trait‐shaped behavioral change [Dinica et al, ]. A remaining question is whether the personality traits modulate brain FC between the SN and other brain regions during internal salience expectation.…”
Section: Introductionmentioning
confidence: 99%
“…This method may also be a relevant means for assessing distractibility in the context of individual differences or clinical populations (Sörqvist and Rönnberg, 2014, Dinica et al., 2015, Forster and Lavie, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…‫الرضا‬ ‫تحقق‬ ‫التي‬ ‫امل‬ ‫العو‬ ‫من‬ ‫التخطيط‬ ‫يعد‬ ‫ذلك‬ ‫إلى‬ ‫باإلضافة‬ ‫ليوت‬ ‫ا‬ ‫و‬ ‫شيلدون‬ ‫اسة‬ ‫در‬ ‫أشارت‬ ‫المثال‬ ‫سبيل‬ ‫فعلي‬ ‫السعادة‬ ‫و‬ (Sheldon & Elliott,1999) ‫الرضا‬ ‫مصادر‬ ‫أحد‬ ‫تعد‬ ‫أهداف‬ ‫تحديد‬ ‫علي‬ ‫الفرد‬ ‫ة‬ ‫قدر‬ ‫إلى‬ ، ‫وشارك‬ ‫وسميث‬ ‫كاسر‬ ‫و‬ ‫شليدون‬ ‫من‬ ‫كل‬ ‫اسة‬ ‫در‬ ‫وتوصلت‬ (Sheldon, Kasser, Smith & Share,2002) ‫تون‬ ‫وهيثر‬ ‫وكوتس‬ ‫أندوي‬ ‫و‬ (Andrew, Coates & Hetherton, 2008) ‫تون‬ ‫بار‬ ‫اسة‬ ‫ودر‬ ( Barton, 2009 Garcia, et,al,2013, Cloninger: ,Lee, & Chae, 2015, Dinica, , Demenescu, ,Lord, Krause, Kaiser, & Horn, 2015, Müller, Panksepp, & Kiefer ,2016 (Gallagher, 2014, Pedrelli, Nyer, David, Jonathan, Holt, Bril, Alert, Fisher, Maurizio & Farabaugh,2015, Chinneck, Thompson, Mahu, Davis-MacNevin, Dobson &, Stewart, 2018Ibrahim & Abdelreheem, 2015, Hassan, 2017 Reed, Bruch & Haase, 2004, Rogers, Creed & Glendon, 2008, Fayga & Kamal, 2011 .) (Cloninger, Svrakic, .& Przybeck,1993, Martin, Magdalena&, Montag,2010, Danilo, Fariba, Sandor, Thomas, Trevor,& Henrik,2015, Cloninger, Granjard, Amato, Mordadi, & Garia,2018 (Michael, et, al, 2001, Sniehotta, et, al 2005 Michael,et,al ,2001) ) .…”
Section: Introductionmentioning
confidence: 99%